Imperializm brytyjski i rosyjski na kartach Vacation tourist Williama George’a Clarka - Jasiakiewicz, Wojciech (Scripta Neophilologica Posnaniensia, 2018)
Imperializm brytyjski i rosyjski na kartach Vacation tourist Williama George’a Clarka